Zinc and chitosan-enhanced β-tricalcium phosphate from calcined fetal bovine bone for mandible reconstruction - Zhou, Jianye; Ma, Rui; Shi, Wen; Lei, Shennan; Zhang, Xiaohui; Jiang, Nan; Lin, Yongsheng; Li, Zhiqiang; Nie, Min (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Mandibular defects pose significant challenges in reconstructive surgery, and scaffold materials are increasingly recognized for their potential to address these challenges. Among various scaffold materials, Beta-tricalcium phosphate (β-TCP) is noted for its exceptional osteogenic properties. However, improvements in its biodegradation rate and mechanical strength are essential for optimal performance. Methods: In this study, we developed a novel β-TCP-based scaffold, CFBB, by calcining fetal bovine cancellous bone. To enhance its properties, we modified CFBB with Chitosan (CS) and Zinc (Zn), creating three additional scaffold materials: CFBB/CS, CFBB/Zn 2+ , and CFBB/Zn 2+ /CS. We conducted comprehensive assessments of their physicochemical and morphological properties, degradation rates, biocompatibility, osteogenic ability, new bone formation, and neovascularization both in vitro and in vivo.Results: Our findings revealed that all four materials were biocompatible and safe for use. The modifications with CS and Zn 2+ significantly improved the mechanical strength, osteogenic, and angiogenic properties of CFBB, while concurrently decelerating its resorption rate. Among the tested materials, CFBB/Zn 2+ /CS demonstrated superior performance in promoting bone regeneration and vascularization, making it a particularly promising candidate for mandibular reconstruction.The CFBB/Zn 2+ /CS scaffold material, with its enhanced mechanical, osteogenic, and angiogenic properties, and a controlled resorption rate, emerges as a highly effective alternative for the repair of oral mandible defects. This study underscores the potential of combining multiple bioactive agents in scaffold materials to improve their functionality for specific clinical applications in bone tissue engineering.